Rural Women as Entrepreneurs in the Context of Patriarchy: Experiences of Female Entrepreneurs in Mudzi District, Zimbabwe - Nyatara, Katherine; Chiweshe, Manase Kudzai; Mahiya, Innocent (Africanus: Journal of Development Studies, 2020)
This article reports on a study which aimed to examine the varied experiences of women involved in business across rural spaces in the context of patriarchy through an exploration of their narratives highlighting their challenges, successes, fears and hopes. The assumption of the study was that rural women in Zimbabwe occupy a particularly difficult space because of numerous structural impediments which include patriarchy, unequal access to skills, capital inadequacy and exclusion from formal economic systems. The study sought to provide a nuanced understanding of female entrepreneurship in African spaces with the aim of showing that there are varied stories of agency, challenges, successes and failures that can be documented. The study utilised qualitative methods which sought a nuanced analysis of women’s experiences in Mudzi District, Mashonaland East Province, Zimbabwe. The data was collected through life histories, focus group discussions and key informant interviews. A total of 34 participants were recruited for the study through purposive and snowball sampling techniques. The participants included women involved in a varied number of entrepreneurial activities such as bread making, vending, dress making, poultry and running micro enterprises. The findings showed that whilst women face multiple structural impediments as entrepreneurs, they are active agents questioning and shaping their social spaces through business. Women embarking on entrepreneurial activities is in itself seen as a serious challenge against patriarchal structures.